Effect of CaO Ratio in Relation to (NH4)H2PO4 and Temperature on Hydroxyapatite from Shells Using The Hydrothermal Method - Rizky Adhitya; Nadindra Putri Meylia Saskirana; Sani Sani; Yelvia Sunarti (Universitas Islam Raden Rahmat, Malang, 2026)
This study investigates the synthesis of hydroxyapatite (HA) from mussel shells using the hydrothermal method, focusing on the CaO to (NH₄)H₂PO₄ ratio and reaction temperature as critical parameters. Increasing seafood consumption in the Surabaya region has resulted in greater shell waste, necessitating the exploration of sustainable practices in utilizing this byproduct for bio-materials, particularly in bone implants. The research employs a hydrothermal approach due to its efficacy in controlling HA crystal morphology and enhancing crystallinity. Experimental findings indicate that the optimal yield of 69.64% occurs at a 1.7 Ca/P ratio and 96 °C, validating the importance of both parameters in achieving adequate material characteristics. XRF and XRD analyses confirm the synthesized HA's chemical composition and a high degree of crystallinity at 81.01%, exceeding the minimum requirements for biomedical applications. However, Ca/P ratios slightly above the standard range suggest incomplete reactions during synthesis. This study makes a new contribution by systematically evaluating the combined effects of the Ca/P precursor ratio and moderate hydrothermal temperature on the synthesis of hydroxyapatite derived from local shell waste in general. The results of this study demonstrate the potential of marine shell waste as a sustainable source of calcium for producing hydroxyapatite with high crystallinity suitable for biomaterial applications, thereby supporting the development of environmentally friendly biomaterials for medical use.